VD_FINDINFO Décision / 2013 / 842 vom 24. März 2011 - VD Tribunal cantonal (2011)
INDEMNITÉEN GÉNÉRAL, AVOCAT D'OFFICE, ASSISTANCE JUDICIAIRE, MODIFICATIONEN GÉNÉRAL | 132 al. 1 let. b CPP (CH), 132 al. 2 CPP (CH), 132 CPP (CH), 429 CPP (CH), 83 CPP (CH)